(untitled) (Homoeopathy for All, 2025)
Tonsillitis is common, especially in children. Tonsillitis is inflammation of the tonsils most commonly caused by viral or bacterial infection. The most common problems affecting the tonsils are recurrent infections (throat or ear) and significant enlargement or obstruction that causes breathing and swallowing problems. The condition can occur occasionally or recur frequently. This article provides an overview of the aetiology, diagnosis, and appropriate general & homoeopathic management of this disorder.